Estudio de Factibilidad para la implementación de un Establecimiento Turístico (LODGE) en el Barrio Ungumiatza, del cantón Yantzaza, provincia de Zamora Chinchipe. - Orellana Acaro, Ángel Ariel (2023)
The general objective of this research work is to carry out a feasibility study for the implementation of a tourist establishment (Lodge) in the Ungumiatza neighborhood, in the Yantzaza canton, province of Zamora Chinchipe, which will benefit the inhabitants of the area. as well as the investors of this business idea. Likewise, to those who make use of it. The specific objectives that were considered in this study were to determine the feasibility of the market study, the technical study, the administrative study and the financial study, which were developed in that order and make up the discussion stage of this work. To develop the methodology, the target population that will be the object of study was identified by calculating the national tourists that make up the economically active population of the middle and upper sector that visit the province of Zamora Chinchipe, for which a total of 21,362 tourists. To whom, through quantitative research and descriptive analysis, it was possible to collect the necessary information for the development of the market study, which allowed us to obtain an unsatisfied demand of 7,067 people who require lodging and food services. The installed capacity was also determined through the technical study, which is 7,488 places per year that make up the entire establishment. That is, 144 places per week, in which 6 days and 24 places per day will be served. However, the capacity that will be used is 4,368 places per year, since the percentage of expected demand is taken into account, since there will be days with high demand and days with low demand. In the administrative study it was established that the human talent that will be required is made up of 13 people who will be distributed in the administrative offices and in the indicated departments. Also, the costs, income, balance point and financial statements were determined through the financial study, where data favorable to the research is presented, starting with an investment equivalent to $203,079.73 of which, 50% will be contributed by the partners. and the other 50% will be financed by a banking entity with an interest rate of 14%. Regarding the Financial Evaluation, the Net Present Value (NPV) is positive $77,961.20; The Internal Rate of Return (IRR) has a higher percentage, compared to the interest rate applied in financing, which is 25.98%. The Capital Recovery Period is 4 years, 1 month and 2 days. The Benefit-Cost Ratio is $1.59 and a Sensitivity Analysis supporting a 21.40% increase in costs and a 13.50% decrease in income. Thanks to this, it is concluded that the feasibility study presents positive results, therefore, the business idea will be recommendable or acceptable to invest in.